PENERAPAN METODE PERMAINAN PLAY DOUGH TERHADAP KREATIVITAS PESERTA DIDIK RA ROUDLOTUL ULUM DESA METATU KECAMATAN BENJENG KABUPATEN GRESIK - Subardjo, Yuliana; Rahayu, Nurul Puji (LPPM Universitas PGRI Adi Buana Surabaya, 2017)
This research was initiated by school educational is education to help growth and development physical and spiritual a child out family environment before entering basic education. One form of play they can develop creativity the son was play dough. The application of metode play dough expected children would prefer in play and learn, because they can develop her creativity higher with as one pleases. Formulation a problem in research this is how the application of metode game play dough to creativity school tuition ra roudhotul ulum located in Dsn. Metatu, Ds. Metatu, Kec. Benjeng Kab. Gersik. This research in a qualitative. Technicque data collection used in penelitian this is obsevasuion and interview. Oeservation and interview used writer to take data about how the application of metode game play dough to creativity school tuition. The result of this research show that with the application of game play dough can home creativity and enhance the spirit of learning to learners. Keywords: Metode Game Play Dough, Creativity.